2021
DOI: 10.1021/acssensors.1c00554
|View full text |Cite
|
Sign up to set email alerts
|

CASPAM: A Triple-Modality Biosensor for Multiplexed Imaging of Caspase Network Activity

Abstract: Understanding signal propagation across biological networks requires to simultaneously monitor the dynamics of several nodes to uncover correlations masked by inherent intercellular variability. To monitor the enzymatic activity of more than two components over short time scales has proven challenging. Exploiting the narrow spectral width of homo-FRETbased biosensors, up to three activities can be imaged through fluorescence polarization anisotropy microscopy. We introduce Caspase Activity Sensor by Polarizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, we also tested Spz cleavage depending on pro-Psh and H 2 O 2 treatment, by co-overexpressing Spz WT or Spz uc and pro-Psh using a single plasmid with the viral P2A sequence between the Spz WT or Spz uc and pro-Psh open reading frames (ORFs) [ 51 , 52 ] (Figs 5A and S7D ). Cleavage of Spz WT occurred depending on H 2 O 2 treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we also tested Spz cleavage depending on pro-Psh and H 2 O 2 treatment, by co-overexpressing Spz WT or Spz uc and pro-Psh using a single plasmid with the viral P2A sequence between the Spz WT or Spz uc and pro-Psh open reading frames (ORFs) [ 51 , 52 ] (Figs 5A and S7D ). Cleavage of Spz WT occurred depending on H 2 O 2 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For pMT-Spz-3xFLAG-P2A-pro-Psh WT and pMT-Spz uc -3xFLAG-P2A-pro-Psh WT , the coding sequences of Spz-3xFLAG or Spz uc -3xFLAG were PCR-amplified from pMT-Spz-3xFLAG or pMT-Spz uc -3xFLAG plasmids, respectively, with GGGSGGG linker and P2A sequences at the 3’ terminus [ 51 , 52 ]. The coding sequence of pro-Psh WT was PCR-amplified from pMT-pro-Psh WT .…”
Section: Methodsmentioning
confidence: 99%
“…Sample preparation and image acquisition: samples correspond to HeLa cells transfected with CASPAM, a cytosolic biosensor described in Habif et al 2021. Imaging was performed by means of a custom built setup as described in Squire et al 2004 andVilar et al 2009.…”
Section: Methodsmentioning
confidence: 99%
“…The most straightforward solution for multiplexing is to employ spectral distinct biosensors that can be easily distinguished based on their fluorescence properties ( Figure 2a ). Habif et al [ 37 ] reported a triple-modality biosensor system, CASPAM, which expresses three differently colored FP-based biosensors in equimolar concentrations. CASPAM enables simultaneous imaging of the activity dynamics of three key nodes in the caspase network.…”
Section: New Approaches For Multiplexed Imaging With Fp-based Biosensorsmentioning
confidence: 99%